Elements of Christian popular piety in Nubia (VI-XVI century) – an outline of aspects - Mich, Katarzyna Anna (Annales Missiologici Posnanienses, 2019)
The study of Christian popular piety in Nubia is very difficult, because after the old Christian communities in Nubia only ruins of churches, towns and villages buried in the desert sand, which are successfully examined by archaeologists from various countries, including Poland. The article presents forms of popular piety from the areas of Nobadia and Makuria, the former Christian kingdoms in the areas of present-day Sudan. Due to the small number of sources, the Alwa kingdom was omitted. The elements presented in this article are merely an outline of popular piety, which, thanks to the research of settlement positions from the period of Christian kingdoms and epigraphical sources, is successfully reconstructed.